Preliminary joint X-ray and neutron protein crystallographic studies of ecDHFR complexed with folate and NADP(+) - Wan, Qun (International Union of Crystallography, 2014)

(untitled)
A crystal of Escherichia coli dihydrofolate reductase (ecDHFR) complexed with folate and NADP(+) of 4 × 1.3 × 0.7 mm (3.6 mm(3)) in size was obtained by sequential application of microseeding and macroseeding. A neutron diffraction data set was collected to 2.0 Å resolution using the IMAGINE diffractometer at the High Flux Isotope Reactor within Oak Ridge National Laboratory. A 1.6 Å resolution X-ray data set was also collected from a smaller crystal at room temperature. The neutron and X-ray data were used together for joint refinement of the ecDHFR–folate–NADP(+) ternary-complex structure in order to examine the protonation state, protein dynamics and solvent structure of the complex, furthering understanding of the catalytic mechanism.